2018
DOI: 10.1021/acschemneuro.8b00219
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Kinetic Isotope Effect Studies of a Potential in Vivo Metabolic Trapping Agent for Monoamine Oxidase B

Abstract: Visualizing the in vivo activity of monoamine oxidase B (MAO-B) is a valuable tool in the ongoing investigation of astrogliosis in neurodegeneration. Existing strategies for imaging changes in MAO enzyme expression or activity have utilized the irreversible suicide inhibitors or high-affinity reversibly binding inhibitors as positron emission tomography (PET) ligands. As an alternative approach, we developed 4-methyl-7-[(1-[C]methyl-1,2,3,6-tetrahydropyridin-4-yl)oxy]-2 H-chromen-2-one ([C]Cou) as a metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…However, the technical challenges of irreversible inhibitors such as deprenyl hinder the accurate image analysis. Several reversible-binding inhibitors have been developed in recent years such as [ 11 C]Cou ( 170 , 219 ), [ 11 C]SL25.1188 ( 168 ), and [ 11 C]SMBT-1 ( 166 ). Harada et al showed a specific increased regional retention of [ 11 C]SMBT-1 in the cortical and hippocampal regions in patients with AD compared to healthy controls ( 166 ).…”
Section: Neuroinflammation Positron Emission Tomography Imagingmentioning
confidence: 99%
“…However, the technical challenges of irreversible inhibitors such as deprenyl hinder the accurate image analysis. Several reversible-binding inhibitors have been developed in recent years such as [ 11 C]Cou ( 170 , 219 ), [ 11 C]SL25.1188 ( 168 ), and [ 11 C]SMBT-1 ( 166 ). Harada et al showed a specific increased regional retention of [ 11 C]SMBT-1 in the cortical and hippocampal regions in patients with AD compared to healthy controls ( 166 ).…”
Section: Neuroinflammation Positron Emission Tomography Imagingmentioning
confidence: 99%
“…There are exceptions to this concern, for example, if the radiotracer is trapped within the tissue and not distributed to plasma. This is exemplified with the radiotracer [ 11 C]Cou for which the polar metabolite is trapped in tissue (Drake et al, 2018).…”
Section: Not Knownmentioning
confidence: 99%
“…However, this radiotracer was not intended for human use due to the severe and largely irreversible toxic effects associated with pharmacological doses of MPTP. The MPTP analog 4-methyl-7-((1-[ 11 C]methyl-1,2,3,6tetrahydropyridin-4-yl)oxy)-2H-chromen-2-one ([ 11 C]Cou) was assessed in rhesus monkeys and found to be selectively metabolized by MAO-B; with the product of MAO-B oxidation and subsequent hydrolysis trapped in the brain (Drake et al, 2018). However, excessive trapping led to time activity curves that were insensitive to the relative density of MAO-B in the brain.…”
Section: Not Knownmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative strategy for radiotracer development toward MAOs, our program at the University of Michigan has investigated the use of metabolic trapping for imaging MAO enzymatic activity . In this approach, a substrate that is freely diffusible across the blood-brain barrier is designed such that the product of MAO oxidation is sufficiently polar to be retained within brain tissues at the sites of enzyme action (Figure ).…”
Section: Metabolic Trapping Mechanismmentioning
confidence: 99%